Stable and Efficient PtRu Electrocatalysts Supported on Zn-BTC MOF Derived Microporous Carbon for Formic Acid Fuel Cells Application - Khan, Inayat Ali; Sofian, Muhammad; Badshah, Amin; Khan, Muhammad Abdullah; Imran, Muhammad; Nadeem, Muhammad Arif (Frontiers in Chemistry, 2020)
Highly efficient, well-dispersed PtRu alloy nanoparticles supported on high surface area microporous carbon (MPC), electrocatalysts were prepared and tested for formic acid oxidation reaction (FAOR). The MPC was obtained by controlled carbonization of zinc-benzenetricarboxylate metal-organic framework (Zn-BTC MOF) precursor at 950 °C and PtRu (30 wt.%) nanoparticles were prepared and deposited via polyol chemical reduction method. The structural and morphological characterization of the synthesized electrocatalysts was carried out using powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray (EDX) technique and gas adsorption analysis (BET) whereas the FAOR performance of the catalysts was investigated through cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS). During the electrochemical measurements, a correlation between high electrochemical surface area and high FAOR performance of the catalysts was observed. Among the materials employed, Pt1Ru2/MPC 950 with high electrochemical surface area (25.3 m2 g–1) consequently showed superior activity of the FAOR (Ir = 9.50 mA cm–2 and Jm = 2403 mA mgPt–1) at room temperature with improved tolerance toward carbonaceous species. The superior electrochemical performance, tolerance to CO-poisoning and long-term stability was attributed to the high surface area carbon support (1455 m2 g–1) and high percent loading of ruthenium (20 wt.%). The addition of Ru promoted the efficiency of electrocatalyst by offering FAOR via bifunctional mechanism.